Spontaneous pathology of the laboratory non-human primate - Bradley, Alys E.; Chilton, Jennifer A.; Mahler, Beth W. (Academic Press, an imprint of Elsevier, 2023)
Spontaneous Pathology of the Laboratory Non-human Primate serves as a "go to" resource for all pathologists working on primates in safety assessment studies. In addition, it helps diagnostic veterinary pathologists rule out spontaneous non-clinical disease pathologies when assigning cause of death to species in zoological collections. Primate species included are rhesus, cynomolgus macaques and marmosets. Multi-authored chapters are arranged by organ system, thus providing the necessary information for continued research. Pathologists often face a lack of suitable reference materials or historical data to determine if pathologic changes they are observing in monkeys are spontaneous or a consequence of other treatments or factors.